Association of anemia with acute lower respiratory tract infection in children aged 2 months to 5 years - Tailor, Dixita; Bamnawat, Subhash; Sareen, Devendra; Jain, Shubham (International Journal of Contemporary Pediatrics, 2023)
Background: In developing countries lower respiratory tract infection (LRTI) is a major cause of death in children. Various risk factors like low birth weight, malnutrition, vitamin A deficiency, lack of breastfeeding, poor socioeconomic status, large family size, young age and air pollution have been proposed for development of lower respiratory infections. Anemia is one of the commonest cofactor of LRTI. Methods: A case-control study was conducted among 150 children in the age group of 2 months-5 years who attended the department of paediatrics during February 2021 to July 2022. Accordingly, 75 cases of LRTI and 75 normal controls (age and gender matched) were enrolled. Their parents were interviewed using a semi-structured questionnaire. Blood investigations were done and documented in a proforma. Results: On studying the age distribution, maximum children were in the age group of 1-3 years. Male preponderance was found with male: female ratio being 1.27:1. Study shows that 74.67% of the cases and 34.67% of the controls were found anemic. Anemia was found to be a significant risk factor for LRTI (p<0.001). Conclusions: Anemia was significantly found in patients with LRTIs and these patients were found to be more susceptible to LRTIs. Prevention of anemia, due to whatever etiology, early diagnosis and treatment is important to reduce the incidence of LRTIs in children.